DEVELOPING COMPUTER SCIENCE UNDERGRADUATE STUDENTS’ COMMUNICATIVE AND SELF-EXPRESSION SKILLS: DIGITAL VS. TRADITIONAL STORYTELLING METHODS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
To succeed in the modern digital workplace, to express ideas clearly and effectively, and to be convincing, university graduates should be equipped with communicative and self-expression skills even if their future jobs do not involve constant communication with different people. Digital and traditional storytelling used in the English language classroom are considered efficient methods for developing these skills among computer science undergraduate students. With the appearance of Artificial Intelligence and free access to various AI tools, creating digital stories is becoming easier and easier, and today’s students, being representatives of the digital era, are proficient with these tools. The research aims to examine computer science undergraduate students’ perceptions of the effectiveness of digital vs. traditional storytelling methods in developing their communicative and self-expression skills. Using the designed paper-based questionnaire, the researchers collected data from 119 first- and second-year computer science undergraduate students. The data were collected during September-October 2024 and the obtained data were processed qualitatively. Results suggest that in today’s English language classroom digital storytelling is a more convenient way of engaging students in expressing their ideas and personal points of view. Presenting their digital stories in front of the class and defending their views provide developing their communicative and self-expression skills. Concerning computer science undergraduate students who prefer writing stories, we can claim that they understand the value of such assignments since they help them gather their thoughts and express them more logically and structured.